STRATEGI MARKETING BANK MUAMALAT DALAM MENARIK NASABAH MELALUI ANALISA SWOT - Nurintan Siregar (EKSYA : Jurnal Ekonomi Syariah, 2021)
This paper discusses the marketing strategy of Bank Muamalat in attracting customers through SWOT analysis. The research method used is field research with a qualitative approach, which focuses on solving appropriate problems regarding the marketing strategy of Bank Muamalat products by collecting primary and secondary data, analyzing the results of data collection and making interpretations and conclusions. The results of this study are that the advantages of the bank muamalat strategy can be seen from the socialization to campuses and schools about bank muamalat programs. Bank Muamalat is also the first pure sharia bank in Indonesia. While the weakness of Bank Muamalat is the lack of facilities and infrastructure such as the number of bank offices, ATM machines, so that many customers wonder what if they want to take cash in savings. If you use a Prima ATM or ATM Bersama, it also requires a fee to take savings. The existence of socialization to campuses and to schools about Bank Muamalat programs is a very good opportunity to attract customers. The existence of the phenomenon of "Ayo Hijrah" makes more and more people to open accounts at Muamalat bank. As the first pure sharia bank, Muamalat bank became a big capital in its marketing strategy to attract customers. Bank Muamalat's challenge is the lack of supporting facilities and infrastructure such as the lack of sub-branches and ATM machines